Positive day-to-day relationships between the cortisol and testosterone awakening responses in elite male athletes - Crewther, Blair T; Serpell, Benjamin G; Obmiński, Zbigniew; McLaren, James; Fourie, Phillip; Cook, Christian J (Biology of Sport, 2025)
The cortisol awakening response (CAR) shows promise as a tool for tracking stress, recovery, and fatigue, although questions around CAR stability in elite sport exist. A functional cortisol link to testosterone and its awakening response (TAR) could also affect the CAR and endpoint outcomes, with stress as a moderating factor. To help resolve these issues, we investigated the day-to-day dynamics of the CAR and TAR in elite athletes and controls. Saliva samples (i.e., waking, waking+30 minutes) were taken from 29 male rugby players (mean age 26.4 years) on four consecutive days and 42 male controls (age 31.0 years) on two consecutive or non-consecutive days. Relative CAR ∆30 and TAR ∆30 were computed as a reactive change score. All of the hormonal variables showed poor short-term stability in elite athletes, with only slight improvements among controls. On average, a significant and similar rising CAR ∆30 was seen in athletes (42.0%) and controls (27.0%), whilst the TAR ∆30 declined similarly in both cohorts by -11.0% and -15.5%, respectively. In elite athletes only, the CAR ∆30 and TAR ∆30 were significantly and positively related, likewise for all other cortisol-to-testosterone variable comparisons (partial r = 0.19–0.45). In summary, substantial daily variation emerged in the relative CAR and TAR, especially in elite male athletes. However, only elite athletes presented positive CAR and TAR relationships that extended to their constituent components. These signals could represent a coordinated system to prepare for and respond to daily stressors in elite sport, which also offers a complex regulatory mechanism for controlling the CAR.